MENINGKATKAN KEMAMPUAN KOGNITIF MELALUI AKTIVITAS SENI MUSIK TERHADAP ANAK KELOMPOK B DI TK. ADINDA CAHAYA CIMAHI - Waraswati, Nurpuri; Andriani, Rini (IKIP Siliwangi, 2018)
Early Childhood Education (PAUD) implements education that refers to all the basic aspects or abilities that are developing in the child. The basic ability of children is very interesting to be studied, one of them cognitive abilities of children. It is raised in connection with the lack of cognitive abilities in Adinda Cahaya kindergarten with the present method mainly through the activity of the art of music. The existing formulation in this study is